Production of Composite Briquette Fuel from Brewery Wastewater Sludge and Spent Grains - Bontu Teshome; Berhanu Assefa; Kenatu Angassa (International Journal of Biomaterials)
Biomass waste energy recovery is a significant method for recycling energy from waste and capturing it for use in renewable energy sources. The abundance of brewing byproducts, such as brewery spent grain (BSG) and brewery wastewater sludge (BWWS), as well as their high carbon concentrations gives these wastes energy potential. With 20% molasses utilized as a binding agent to maximize the high caloric value of the briquette, this study sought to examine the quality of mixed briquettes made from BSG and BWWS. In order to make composite briquettes with a maximum caloric content of 19.94 MJ/kg, the ideal conditions were chosen, which included a temperature of 350°C, a production period of 60 min, and a 75% BSG mixing ratio. It can be compared to sawdust briquettes, which have a calorific value of 22.88 MJ/kg, by looking at the calorific value of densified with pressure 100 bar for mixed carbonized briquettes vs mixed noncarbonized briquettes (21.13 MJ/kg). The value of R2 was 0.9607 and indicated that 96.07% of the total validation in the calorific value correlation between experimental and predicted values. The finding of the study showed that the efficiency of the quadratic model in fitting the data would be higher under the conditions of the experiment. Based on ISO 17225-6 fuel quality classes and specifications for graded nonwoody pellets, the study concluded that using BSG and BWWS as alternative energy sources meets those requirements.